2015
DOI: 10.1590/0103-6440201300409
|View full text |Cite
|
Sign up to set email alerts
|

Vital Pulp Therapies in Clinical Practice: Findings from a Survey with Dentist in Southern Brazil

Abstract: Studies based on dentists' clinical practice possess vital relevance to understand factors leading the clinicians to choose by a specific technique over another. This study investigated which clinical conduct therapies are adopted by dentists in front of deep caries. Was evaluated how the place of work, post-graduate training and years since complete graduation influenced their decisions. A cross-sectional study was performed using a self-applied questionnaire with dentists (n=276) in Southern Brazil. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
3
31
0
4
Order By: Relevance
“…Symptomatic irreversible pulpitis and necrotic pulp are the most common clinical diagnostic conditions for patient undergoing root canal treatment; this was in agreement with the findings Khattak et al 18 who reported an occurrence of necrosed pulp (38.31%) was the most common reason for root canal treatment followed by irreversible pulpitis (34.28%), the reason is both are sequel of dental caries which considered the most common cause of pulp damage and requiring root canal treatment 19,20,21 .…”
Section: Fig 3: Radiographic Evaluation Of Pulpal and Periapical Tissuesupporting
confidence: 84%
“…Symptomatic irreversible pulpitis and necrotic pulp are the most common clinical diagnostic conditions for patient undergoing root canal treatment; this was in agreement with the findings Khattak et al 18 who reported an occurrence of necrosed pulp (38.31%) was the most common reason for root canal treatment followed by irreversible pulpitis (34.28%), the reason is both are sequel of dental caries which considered the most common cause of pulp damage and requiring root canal treatment 19,20,21 .…”
Section: Fig 3: Radiographic Evaluation Of Pulpal and Periapical Tissuesupporting
confidence: 84%
“…Several strategies and approaches to use regenerative therapies in dentistry have been investigated (1)(2)(3), since that materials employed by the clinicians are, basically, synthetic (4)(5)(6) and can present limited ability to induce regeneration (1,3,7). Thus, the use of MSC could improve the regenerative potential of bone, periodontal and dental pulp regenerative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These GDPs could be more updated with the recent literatures. The influence of the time since graduation and place of work on the clinical conduction related to caries removal and choice of materials has also been reported by Chisini et al (2015). VPT, which includes stepwise excavation, indirect pulp capping, direct pulp capping, miniature pulpotomy, partial/Cvek pulpotomy and coronal/complete pulpotomy, has been considered an ultraconservative treatment in modern endodontics ( .…”
Section: Discussionmentioning
confidence: 96%
“…VPT, which includes stepwise excavation, indirect pulp capping, direct pulp capping, miniature pulpotomy, partial/Cvek pulpotomy and coronal/complete pulpotomy, has been considered an ultraconservative treatment in modern endodontics ( . There has been a discrepancy between general dentists regarding pulp capping material selection in VPT which has been recently reported in Brazilian general dentists (Chisini et al 2015). They have pointed out that none of the dentists who are working exclusively in the public health system choose expensive material, such as mineral trioxide aggregate (MTA), as the capping material.…”
Section: Discussionmentioning
confidence: 99%